2023
DOI: 10.4081/ija.2022.2173
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the impact of soil salinity: recent developments and future strategies

Abstract: Soil salinity is among the major abiotic stresses that plants must face, mainly in arid and semiarid re-gions, and high salinity tolerance is an important agronomic trait to sustain food production. Agricul-tural soils are unstable and subject to changes in salinity level, and monitoring them at both the local and the regional scale is a relevant activity to adopt soil and water management strategies to decrease salt concentration in the root zone, thus minimizing impacts on plant growth and productivity. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…As reported by Tedeschi et al (2023) beneficial soil microorganisms, such as arbuscular mycorrhizal fungi and plant growthpromoting bacteria, when present in saline environments, can alle- Furthermore, it has been shown that biostimulants can alleviate the detrimental effect of salinity on plant growth and production. Treatments with increasing levels of salt concentration in irrigation water combined with foliar biostimulant treatments on wild arugula investigated by Sifola et al (2023) showed how plant response appears to depend on biostimulant application, growth conditions, and genetic traits in secondary salinity contexts.…”
mentioning
confidence: 96%
“…As reported by Tedeschi et al (2023) beneficial soil microorganisms, such as arbuscular mycorrhizal fungi and plant growthpromoting bacteria, when present in saline environments, can alle- Furthermore, it has been shown that biostimulants can alleviate the detrimental effect of salinity on plant growth and production. Treatments with increasing levels of salt concentration in irrigation water combined with foliar biostimulant treatments on wild arugula investigated by Sifola et al (2023) showed how plant response appears to depend on biostimulant application, growth conditions, and genetic traits in secondary salinity contexts.…”
mentioning
confidence: 96%